1929
DOI: 10.1084/jem.49.6.959
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Versus Subcutaneous Immunization of Monkeys Against Poliomyelitis

Abstract: Early experiments of Flexner and Lewis (1), Levaditi and Landsteiner (2), and RSmer and Joseph (3) showed that monkeys once recovered from poliomyelitis are immune to subsequent intracerebral inoculations of poliomyelitis virus. This immunity was apparent no matter how slight had been the symptoms of the initial infection. The refractory state was of long duration and was absolute within the limit of infecting doses employed. These same workers noted that sera of convalescent monkeys, when mixed with poliomyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1932
1932
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…While poliovirus serotypes are defined by neutralization assays, the lack of cross-neutralization is not absolute: individual serotypes may be incompletely neutralized by antibodies raised against the other two serotypes ( 28 ), suggesting that antibodies able to neutralize multiple strains of poliovirus can be identified. Results from studies done in the 1920s and 1930s by Stewart and Rhoads, Aycock, and Burnet and Macnamara in which monkeys were infected with either the 1909 “MA” isolate of poliovirus from a fatal case of poliomyelitis, the Vermont “Aycok” isolate from 1920, or the Australian “Victoria” virus identified in 1928 and challenged with infection by a heterologous isolate provide evidence for some cross-protection among serotypes ( 29 31 ). Additionally, monospecific polyclonal sera from seven monkeys, each immunized with an individual untyped viral isolate from patients during the 1949 poliomyelitis outbreak in Kansas City, were found to partially neutralize more than one prototype poliovirus ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…While poliovirus serotypes are defined by neutralization assays, the lack of cross-neutralization is not absolute: individual serotypes may be incompletely neutralized by antibodies raised against the other two serotypes ( 28 ), suggesting that antibodies able to neutralize multiple strains of poliovirus can be identified. Results from studies done in the 1920s and 1930s by Stewart and Rhoads, Aycock, and Burnet and Macnamara in which monkeys were infected with either the 1909 “MA” isolate of poliovirus from a fatal case of poliomyelitis, the Vermont “Aycok” isolate from 1920, or the Australian “Victoria” virus identified in 1928 and challenged with infection by a heterologous isolate provide evidence for some cross-protection among serotypes ( 29 31 ). Additionally, monospecific polyclonal sera from seven monkeys, each immunized with an individual untyped viral isolate from patients during the 1949 poliomyelitis outbreak in Kansas City, were found to partially neutralize more than one prototype poliovirus ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stewart and Rhoads (61) 20 % suspension of virus (strain unspecified). One developed paralysis from the vaccine.…”
Section: A Methodsmentioning
confidence: 99%
“…The results of many efforts to induce resistance in Macacus rhesus monkeys against experimental poliomyelitis by means of inoculations of virus in one form or another have been summarized by Stewart and R_hoads (1929) (1) and in the volume published by the Milbank International Committee (1932) (2). What may be derived from these experiments, beginning with the first, undertaken 25 years ago by Flexner and Lewis (3), is that "it is impossible to protect monkeys by the use of killed virus and second, that a definite though inconstant resistance to poliomyelitis can be brought about by the intradermal and subcutaneous introduction of the living virus" (1). The fact also emerges from the numerous trials hitherto reported that resistance is acquired by monkeys when a sufficient amount of active virus is given intra-or subcutaneously in one massive dose (3,4)or in smaller amounts repeated over a considerable period of time (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The fact also emerges from the numerous trials hitherto reported that resistance is acquired by monkeys when a sufficient amount of active virus is given intra-or subcutaneously in one massive dose (3,4)or in smaller amounts repeated over a considerable period of time (3)(4)(5)(6). Even then protection is not afforded to some animals and the degree of immunity induced varies in others, while now and again a treated monkey succumbs to the disease as a result of the inoculations (1,(5)(6)(7)(8).…”
mentioning
confidence: 99%